Synergy between orthodontics and dentistry: Integrative approaches for superior results - Lindoso, Caio Silva; Fonseca, Anne Caroline dos Santos; França, Suene Teixeira Jansen; Araújo, Jéssica Raíssa Leal; Lindoso, Larissa Silva; Lindoso, Kauê Silva; Barros, Laysa da Cunha (Seven Editora, 2024)
Every procedure performed in Cosmetic Dentistry is expected to restore function and aesthetics to the patient, which is why interdisciplinary care involving more than one specialty contributes to better results. Cosmetic dentistry and orthodontics work synergistically, such as in aesthetic smile planning, cases of bruxism, diastema, final restorations after orthodontic treatment, bite and occlusion adjustment and treatment of missing or damaged teeth. Therefore, the objective of the present study will be to analyze and cite scientific productions that address the importance of the integrative approach between cosmetic dentistry and orthodontics, going beyond appearance and reaching more complex issues regarding specialties and the way they correlate to clinical solutions. of pathologies and functional aesthetic planning. DOI:https://doi.org/10.56238/sevened2023.006-124